A STUDY ON INTESTINAL OBSTRUCTION REGARDING ITS EPIDEMIOLOGY, ETIOLOGY AND MANAGEMENT IN A PERIPHERAL MEDICAL COLLEGE - AHMAD, MD; BARMAN, AMALESH; SINHA, PANKAJ KUMAR; SAHA, ANIL KR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The intestinal obstruction is a widespread emergency problem in our surgical practice day by day. It is a significant cause of morbidity and mortality in our health system. It is caused by adhesions, hernias, malignancies, endometriosis, inflammatory bowel disease stenosis, intussusception, and others. Our research aims to identify the etiology, epidemiology, and clinical presentations of the pathology so that we can manage the disease as early as possible for better outcomes in our peripheral institution. Methods: The study was performed on 100 cases of the age group 12–76 years admitted in the surgical ward of Midnapore Medical College and Hospital, Paschim Medinipur (W.B.) from December 2016 to June 2018. Cases of acute intestinal obstruction who underwent operation were included in our research to establish the pathology of intestinal obstruction. Results: In our study, the incidence of acute intestinal obstruction is 1.6% of total surgical cases. Maximum patients (25%) were in the age group 51– 60 years. The most common cause of intestinal obstruction was obstructed/strangulated hernia (40%). The most common symptoms were pain abdomen (88%), abdominal distension (84%), and vomiting (78%). An X-ray revealed presence of air-fluid levels in 75% of patients. The overall mortality rate was 10%. Conclusion: The morbidity and mortality of intestinal obstruction are dependent on early diagnosis, prompt resuscitation, and proper management. The critical determinants of the morbidity are age of the patient, duration of the disease, existing comorbidity, and delay in treatment. X-ray in erect view is an essential mode of diagnostic method and obstructed hernia is the most common etiology of obstruction in our research study.